2018
DOI: 10.1080/20004508.2018.1475200
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking in national tests across four subjects in Swedish compulsory school

Abstract: Critical thinking is brought to the fore as a central competence in today's society and in school curricula, but what may be emphasised as a general skill may also differ across school subjects. Using a mixed methods approach we identify general formulations regarding critical thinking in the Swedish curriculum of school year nine and seven more subject-specific categories of critical thinking in the syllabi and national tests in history, physics, mathematics and Swedish. By analysing 76 individual students' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
5

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
1
21
0
5
Order By: Relevance
“…Also, in upper-secondary schooling, Swedish students at more advanced level (History 2 & 3) may struggle with test questions designed to assess historical thinking (Rosenlund, 2016). Lack of domain-specific knowledge can make it hard for students to contextualise historical sources, to understand temporal dimensions of the past and critically scrutinise information in relevant ways (Nygren, Haglund, Samuelsson, Af Geijerstam, & Prytz, 2018;Rosenlund, 2016).…”
Section: Previous Researchmentioning
confidence: 99%
“…Also, in upper-secondary schooling, Swedish students at more advanced level (History 2 & 3) may struggle with test questions designed to assess historical thinking (Rosenlund, 2016). Lack of domain-specific knowledge can make it hard for students to contextualise historical sources, to understand temporal dimensions of the past and critically scrutinise information in relevant ways (Nygren, Haglund, Samuelsson, Af Geijerstam, & Prytz, 2018;Rosenlund, 2016).…”
Section: Previous Researchmentioning
confidence: 99%
“…In theory and practice, scholars have outlined different aspects of disciplinary literacy that are necessary for evaluating information in different academic subjects. This research highlights how expertise in a discipline includes content knowledge, skills, and attitudes (Nygren, Haglund, et al, 2019;Shanahan et al, 2011;Wineburg, 1991Wineburg, , 1998. Among experts, it has been noted that fact-checkers are particularly skilled at using digital resources to double check information (i.e., read laterally); moreover, they are able to corroborate information in more skillful ways than trained historians (Wineburg & McGrew, 2019).…”
Section: Previous Researchmentioning
confidence: 89%
“…The importance of literacy and academic literacy has been underscored in previous research (Cummins & Swain, 2014;Moje, 2007;Shanahan & Shanahan, 2012). Students' abilities to determine credibility has been linked to their disciplinary literacy, for example, their subject specific knowledge and habits of mind (Nygren & Guath, 2019;Nygren, Haglund, et al, 2019). In theory and practice, scholars have outlined different aspects of disciplinary literacy that are necessary for evaluating information in different academic subjects.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to overestimation of content-specific knowledge, overestimation of digital media literacy skills is also a challenge when it comes to thinking critically. Nygren and Guath (2019 [163]) studied teenagers' ability to determine digital news credibility and found that participants generally assessed themselves very favourably for their information sourcing and evaluating abilities. However, this was negatively correlated with their actual performance in detecting false news in climate change articles, and bias in digital news sources.…”
Section: Relationship Between Self-reported and Actual Abilitiesmentioning
confidence: 99%